(untitled) (Jurnal Bahasa, 2025)
Classifiers play a significant role in the daily interactions of Malaysians as they reflect the nation’’ ethnic, cultural, and linguistic diversity. The Malay classifier "biji" is commonly used for small and round objects, especially fruits. However, previous studies point to a decline in classifiers comprehension across generations. This study aims to identify the level of understanding of the classifier "biji" among the Chinese community in Peninsular Malaysia and to analyse the influence of Mandarin based on Lado’s (1957) theory of transfer and interference. A questionnaire was administered to 400 native speakers of Malaysian Mandarin Chinese from four geographical zones in Peninsular Malaysia. The questionnaire items were constructed using definitions and examples from authoritative Malay classifier dictionary to ensure validity. The findings indicate that the level of understanding of the classifier "biji" among the Chinese community in Peninsular Malaysia is low and has not reached a satisfactory standard. In terms of Mandarin influence, negative transfer occurred more frequently than positive transfer. Mandarin was found to contribute to negative transfer for all classifiers examined, except for the use of "biji" referring to commonly known small and round objects. These findings provide important implications for the pedagogy of teaching Malay and Chinese as second languages, particularly in relation to the semantic influence of learners’ first language. Keywords: Malay classifier, biji, Peninsular Malaysia, Malaysian Chinese community, level of proficiency, contrastive analysis Full text: PDF